Relevance of Carcinogen-Induced Preclinical Cancer Models - Raj N. Sewduth; Konstantina Georgelou (MDPI AG, 2024)
Chemical agents can cause cancer in animals by damaging their DNA, mutating their genes, and modifying their epigenetic signatures. Carcinogen-induced preclinical cancer models are useful for understanding carcinogen-induced human cancers, as they can reproduce the diversity and complexity of tumor types, as well as the interactions with the host environment. However, these models also have some drawbacks that limit their applicability and validity. For instance, some chemicals may be more effective or toxic in animals than in humans, and the tumors may differ in their genetics and phenotypes. Some chemicals may also affect normal cells and tissues, such as by causing oxidative stress, inflammation, and cell death, which may alter the tumor behavior and response to therapy. Furthermore, some chemicals may have variable effects depending on the exposure conditions, such as dose, route, and duration, as well as the animal characteristics, such as genetics and hormones. Therefore, these models should be carefully chosen, validated, and standardized, and the results should be cautiously interpreted and compared with other models. This review covers the main features of chemically induced cancer models, such as genetic and epigenetic changes, tumor environment, angiogenesis, invasion and metastasis, and immune response. We also address the pros and cons of these models and the current and future challenges for their improvement. This review offers a comprehensive overview of the state of the art of carcinogen-induced cancer models and provides new perspectives for cancer research.